THE USAGE OF COORDINATION IN THE STRUCTURE OF THE COMPOSITE SENTENCE - Davronova Dilnoza Shavkat Qizi (Journal of new century innovations, 2022)
The article deals with the the process of coordination, simply stated, involves the linking of structures of equal grammatical rank – single words and phrases in elementary compound groups or independent clauses in compound sentences.